Ethyl (2E)-2-cyano-3-(4-methoxyphenyl)acrylate - P. A. Suchetan; B. S. Palakshamurthy; N. R. Mohan; S. Madan Kumar; N. K. Lokanath; S. Sreenivasa (Acta Crystallographica Section E, 2013)
In the title compound, C13H13NO3, the conformation across the C=C bond is synperiplanar, the torsion angle of the segment C(ring)—C=C—C(N) being 3.2 (5)°. In the crystal, molecules are linked into inversion dimers, arranged in a zigzag pattern, through two C—H...O interactions generating R22(10) and R22(14) motifs. These dimers are arranged in a zigzag pattern in the crystal structure. The molecules are further linked along the c axis through weak C—H...π interactions, and weak π...π interactions [centroid–centroid separation = 3.9986 (17) Å] are also observed.